2014
DOI: 10.2174/1567205011666140131123653
|View full text |Cite
|
Sign up to set email alerts
|

Amygdalar Atrophy in Early Alzheimer’s Disease

Abstract: Current research suggests that amygdalar volumes in patients with Alzheimer's disease (AD) may be a relevant measure for its early diagnosis. However, findings are still inconclusive and controversial, partly because studies did not focus on the earliest stage of the disease. In this study, we measured amygdalar atrophy in 48 AD patients and 82 healthy controls (HC) by using a multi-atlas procedure, MAPER. Both hippocampal and amygdalar volumes, normalized by intracranial volume, were significantly reduced in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
26
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 50 publications
(29 citation statements)
references
References 79 publications
(154 reference statements)
3
26
0
Order By: Relevance
“…However, NAR pre-treatment significantly protected rat recognition memory possibly by protecting cortical neurodegeneration produced by AlCl 3 and D-gal. Regions that are mainly affected in AD brain are cortex, hippocampus, and amygdala [51,52]. We found that in AD-like model rat's associative memory was severely impaired whereas NAR protected rat's associative memory in AlCl 3 +D-gal induced cognitive deficits in PAT.…”
Section: Discussionmentioning
confidence: 73%
“…However, NAR pre-treatment significantly protected rat recognition memory possibly by protecting cortical neurodegeneration produced by AlCl 3 and D-gal. Regions that are mainly affected in AD brain are cortex, hippocampus, and amygdala [51,52]. We found that in AD-like model rat's associative memory was severely impaired whereas NAR protected rat's associative memory in AlCl 3 +D-gal induced cognitive deficits in PAT.…”
Section: Discussionmentioning
confidence: 73%
“…Amygdala volume is significantly reduced in AD in a similar magnitude to the hippocampus (Klein-Koerkamp et al, 2014). However, we have previously shown that amygdala atrophy is not identified over a 2 year follow-up period in elderly population samples, which contrasts with significant atrophy in the hippocampus (Jiang et al, 2014a).…”
Section: Discussionmentioning
confidence: 99%
“…Although the hippocampus has traditionally captured more attention than the amygdala, both structures are critically involved in memory processes and present a similar degree of volume loss in AD3435. Nevertheless, it remains to be determined whether amygdala atrophy, like hippocampal atrophy36, accounts for the emotional changes occurring with disease progression.…”
Section: Discussionmentioning
confidence: 99%